(untitled) (Nigerian Journal of Physiological Sciences, 2019)
Summary: Haematological and serum biochemical values are useful guides and biomarkers in health and diseases for reaching a diagnosis, estimating disease prognosis and monitoring treatment progress, in mammals. Reference ranges for some parameters differ among species of mammals and between sexes within a species. There is dearth of information on standard reference value for blood parameters for Nigerian indigenous monkeys. Whole blood and serum samples obtained from 50 apparently healthy adult monkeys in both captivity and from the wild in southwest Nigeria were subjected to haematology and serum biochemistry to obtain preliminary reference values for haematological and serum biochemical analytes for Cercocebus sebaeus (Green monkey), Cercopithecus mona (Mona monkey), Erythrocebus patas (Patas monkey) and Papio anubis (Anubis baboon). Numerical data were summarized as mean and standard deviation and subjected to statistical analysis; Student t test and analysis of variance, to compare values of blood parameters obtained between species and gender. A p-value less than 0.05 was considered significant. The hematocrit of male animals were significantly higher than that of females (P=0.01) in all the 4 species studied but there was no significant difference in other blood parameters such as total white blood cell and the differential counts, platelet count, serum aspartate transferase, alanine transferase, alkaline phosphatase, total plasma protein, albumin, and globulin concentrations between the sexes. Generally, there was no significant difference between total white blood cell and the differential counts, hematocrit, red cell count, haemoglobin concentration, platelet count, serum aspartate transferase, alanine transferase, alkaline phosphatase, total plasma protein, albumin, and globulin concentrations among the monkey species